Experimental measures of intra-household resource control - Ambler, Kate; Jones, Kelly M.; Recalde, María P. (Elsevier, 2024)
We study experimental measures of preferences for intra-household resource control among 3387 couples in Ghana and Uganda. We implement two incentivized tasks: (1) a game that measures willingness to pay for resource control in the household, and (2) dictator games played privately and jointly by spouses. Across study sites we find that women exhibit a higher willingness to pay for resource control than their husbands and have less influence over joint dictator game decisions. Importantly, behavior in the two tasks is correlated, suggesting that they capture similar underlying latent variables. In Uganda, experimental measures from both tasks are also robustly correlated with a range of survey measures of women's access to resources, agency, and wellbeing. This is not the case in Ghana, suggesting that contextual factors may be important, and researchers may want to collect both measures in a project. Like other recent papers, we find that an important fraction of respondents display negative willingness to pay for intra-household resource control. Our analysis shows that such behavior is displayed by women who have higher levels of economic empowerment and wellbeing, a result that contradicts previous conjectures made in the literature. Altogether, our analysis suggests that, despite lacking ideal theoretical properties, private dictator game decisions (even when collected only from the wife) can perform well as proxies of empowerment.